PELATIHAN INFOBMKG UNTUK PENINGKATAN KESIAPSIAGAAN CUACA DAN GEMPA PADA KARYAWAN HOTEL - Ary Setyoko; Arda Yuswantoro; Deni Permana; Zairo Hendrawan; Dwi Joko Nurdadi; Arafah (Abdi Jurnal Publikasi, 2026)
This community service program aimed to improve disaster-information literacy among employees of Mercure Jakarta Gatot Subroto Hotel by training the use of the official InfoBMKG mobile application. Hotels in dense urban areas are highly exposed to hydrometeorological hazards, air‑quality deterioration, and seismic events, while frontline staff often lack the skills to access and interpret real‑time official data. The program used a one‑day interactive workshop (40% theory; 60% practice) followed by one week of online mentoring. Thirty employees from Front Office, Housekeeping, Food & Beverage, and Security participated. Evaluation applied a pre‑test/post‑test, direct performance observation during hands‑on sessions, and a satisfaction questionnaire. Results show a substantial increase in knowledge: the average score rose from 45.6% (pre‑test) to 82.3% (post‑test), exceeding the 35% improvement target. Participants’ confidence in making operational decisions based on weather, air‑quality, and earthquake information also increased markedly. A key output was the revision of the Hotel Safety SOP by integrating BMKG early‑warning procedures and establishing an internal dissemination channel via WhatsApp; the average response time to alerts decreased from around 2 hours to 25 minutes. The program demonstrates that practical, context‑based training on government digital services can strengthen operational resilience and service quality in the hospitality sector.